A Qualitative Inquiry into the Eating Behavior and Physical Activity of Adolescent Girls and Boys in Indonesia. Issue 1 (June 2021) - Roshita, Airin; Riddell-Carre, Peter; Sjahrial, Revyani; Jupp, Dee; Torlesse, Harriet; Izwardy, Doddy; Rah, Jee Hyun
Background: Despite the rising double burden of malnutrition, adolescent nutrition has received little attention in Indonesia. Eating and physical activity behaviors established in adolescence are known to track into adulthood and may contribute to chronic diseases in later life. This study aimed to explore the eating behaviors and physical activity of Indonesian adolescents, and their influencing factors. Methods: The study, designed as a qualitative study, was conducted in 2 selected districts in Indonesia: Klaten and Lombok Barat. Data were collected through immersion, open and informal discussions, and participant observations with 302 adolescent girls and boys. Results: The eating and physical activity behaviors of adolescent boys and girls are influenced by contextual changes in their family lifestyles and environment. The adolescents in this study only conflate physical activity with participation in sport. Even when a wider view of physical activity is cast, their level of physical activity remains low, especially for adolescent girls. Adolescents and their families generally eat 3 meals a day, with schools an important source of food for adolescents. Adolescents skip breakfast at home, and breakfast and lunch are usually purchased and eaten at school. Fewer families cook and families rarely eat together due to increasingly busy lives, increased mobility, and digital connectivity. Conclusions: The rapid contextual shifts taking place in Indonesia influence the home, school, and peer environment to shape eating behaviors and physical activity among adolescent boys and girls. Gender-responsive multicomponent school-based interventions have the potential to serve as an important entry point for influencing adolescent nutrition.